Semiparametric analysis of German East-West migration intentions: Facts and theory - Michael C. Burda; Wolfgang Härdle; Marlene Müller; Axel Werwatz (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1997)
East-West migration in Germany peaked at the beginning of the 90s although the average wage gap between Eastern and Western Germany continues to average about 25%. We analyze the propensity to migrate using microdata from the German Socioeconomic Panel. Fitting a parametric Generalized Linear Model (GLM) yields nonlinear residual behavior. This finding is not compatible with classical Marshallian theory of migration and motivates the semiparametric analysis. We estimate a Generalized Partial Linear Model (GPLM) where some components of the index of explanatory variables enter nonparametrically. We find the estimate of the nonparametric inuence in concordance with a number of alternative migration theories, including the recently proposed option-value-of-waiting theory.
urn:nbn:de:kobv:11-10056374
Keywords: 330